Sistem Pendukung Keputusan Siswa Berprestasi SMA Dwijendra Denpasar dengan Metode ANP & Topsis - ,; ,; , (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2017)
Realizing the competitive school, grade and achievement is one of the mission and vision that should be applied in schools, especially in the person of the student. To realize the desire that every school needs to evaluate, improve further the service good about teaching techniques, assessment, quality assurance in order to make the school about the competitive, quality and achievement. In this case homeroom faced with a problem in the quality assessment of each student according to the desired criteria of the school. Guardian Class and a burden for the many choices in deciding which is more priority and should be compared so that can not be timely in its completion. Guardian Class here to vote counting and determine their own rank 1 to 10 both for class XI IPA U1 and U2 in high school Dwijendra Denpasar. Determination of students can be categorized as cases of multiple criteria because there are several factors that lead to various alternative options with the values are different, so we need a technology determining student achievement by using ANP and combined with TOPSIS to help the Guardian Class manage ratings in order to take decisions appropriately. In the selection of outstanding students ANP implementation of the method used to determine the effect of the relationship between the criteria of independence while TOPSIS method is used to determine perengkingan in student achievement in each class. The selected outstanding students here are students assessed on three criteria, namely the assessment of knowledge, skills, and attitudes. The average value obtained by the students are very influential in determining student achievement. Manual calculations (regular) can be used if students get the average value in each of the same criteria, but if the average value is different then the manual calculation is not the right way diguankan to determine student achievement, because it will produce accounts that are not consistent in determining student achievement.